Assessing the validity of simplified heating and cooling demand calculation methods: The case of Passive House Planning Package (PHPP) and Radiant Time Series Method (RTSM) - Al Shawa, Bashar (Frontiers in Built Environment, 2024)
To align the buildings sector with the 1.5°C climate change trajectory, enormous improvements in energy efficiency are needed. It is therefore crucial that the tools used to evaluate buildings’ energy use undergo robust testing. This paper tests, for the first time, the outcome of the Passive House Planning Package (PHPP) and an author-modified version of the Radiant Time Series Method (RTSM), following the Building Energy Simulation Test (BESTEST). The results show that while the validity of the modified-RTSM is slightly superior to that of the PHPP, both tools pass less than 35% of the cases – necessitating further calibration and challenging the widely-held belief that the PHPP is ‘validated’. As the PHPP and the modified-RTSM present a relatively simple and quick way of evaluating buildings’ energy performance, calibrating their methodologies so they pass the BESTEST cases could put them at an advantage over the fully dynamic and resource-intensive tools.